Quality of home stimulation and language development in children aged 12-24 months living in orphanages and family homes - Yuridyah P. Mulyadi; Soedjatmiko Soedjatmiko; Hardiono D. Pusponegoro (Indonesian Pediatric Society, 2009)
Background Language development is fundamental for children'sintellectual development. Therefore, early stimulation in thefirst three years of life play an important role especially indisadvantaged communities such as foster homes.Objective To determine the quality of home stimulation andlanguage development, and their correlations in children livingin orphanages and family homes.Methods This study was conducted between December 2007 andJanuary 2008. Subjects were recruited from several orphanagesin Jakarta, Tangerang, Bogor, also three posyandus in Jakarta andTangerang. The quality of home stimulation was assessed usingHome Stimulation Observation for the Measurement of theEnvironment (HOME) scores, while language development wasassessed using Clinical Linguistic and Auditory Milestone ScaleDevelopment Quotient (CLAMS DQ).Results A total of 80 healthy children, consisting of 40 childrenin orphanages and 40 in family homes were enrolled. Inadequatestimulation and language delay were found to be significantlyhigher in the orphanage group (52.5% vs. 27.5%; P=0.022 and57.5% vs. 10%; P<0.001, respectively). HOME Scores andCLAMS DQ were also significantly lower in the orphanagegroup compared to those in the family home group (25.6 vs31.5; P<0.001 and 84.0 vs 110.7; P=0.002). Logistic regressionrevealed that caregiver-child attachment time was the onlyrisk factor for language delay (OR 32.32; P<0.0001), in bothorphanages and family homes.Result The quality of home stimulation is lower in the orphanages,which results in a higher rate of language delay in children aged12-24 months.